2012
DOI: 10.4238/2012.may.15.9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and initial characterization of SOX2-overexpressing NT2/D1 cell clones

Abstract: ABSTRACT. SOX2, a universal marker of pluripotent stem cells, is a transcription factor that helps control embryonic development in vertebrates; its expression persists in neural stem/progenitor cells into adulthood. Considering the critical role of the SOX2 transcription factor in the regulation of genes required for self-renewal and pluripotency of stem cells, we developed and characterized SOX2-overexpressing NT2/D1 cell clones. Using Southern blot and semiquantitative RT-PCR, we confirmed integration and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Accordingly, SOX2 overexpression reduced the level of OCT4 and NANOG in human ESCs (Adachi et al, 2010). In line with this data, we detected downregulation of OCT4 gene expression in pluripotent embryonal carcinoma stem cells NT2/D1 with constitutive SOX2 overexpression (Drakulic et al, 2012). We also demonstrate that transition from proliferation to retinoic acid (RA) induced neural differentiation of NT2/D1 cells coincides with complete OCT4 down-regulation (Stevanović et al, 2017).…”
Section: Sox Proteins and Pluripotencysupporting
confidence: 78%
See 2 more Smart Citations
“…Accordingly, SOX2 overexpression reduced the level of OCT4 and NANOG in human ESCs (Adachi et al, 2010). In line with this data, we detected downregulation of OCT4 gene expression in pluripotent embryonal carcinoma stem cells NT2/D1 with constitutive SOX2 overexpression (Drakulic et al, 2012). We also demonstrate that transition from proliferation to retinoic acid (RA) induced neural differentiation of NT2/D1 cells coincides with complete OCT4 down-regulation (Stevanović et al, 2017).…”
Section: Sox Proteins and Pluripotencysupporting
confidence: 78%
“…Constitutive Sox2 expression kept NPCs in a precursor state and inhibited neuronal differentiation, while expression of a dominant-interfering form of Sox2 led to exit from cell cycle, delamination of NPCs from the ventricular zone, loss of expression of progenitor markers and initiation of neuronal differentiation (Graham et al, 2003). We showed that constitutive SOX2 overexpression altered expression of neuronal markers and reduced number of mature MAP2 (Microtubule Associated Protein 2) positive neurons upon RA induced neural differentiation of NT2/D1 cells (Drakulic et al, 2012;Klajn et al, 2014). Schematic illustration of stepwise neuronal differentiation process (left) and glial differentiation process (right).…”
Section: The Roles Of Sox Transcription Factors In Neuronal Differentmentioning
confidence: 77%
See 1 more Smart Citation
“…One μg of the total RNA was reversely transcribed using the High Capacity cDNA Reverse Transcription Kit (Applied Biosystems, USA) according to the manufacturer's protocol. SOX3 (SRY (sex determining region Y)-box 3) was amplified from the synthesized cDNAs with primers: 5'-CAC GGG TCC TCC GGG TTG CGA GGG GCG GAC C-3' (forward) and 5'-TGG GGA ACA AGG GTG GAC GAG C-3' (reverse); glial fibrillary acidic protein (GFAP) with primers: 5' -GCA GAG ATG ATG GAG CTC AAT GAC C-3' (forward) and 5'-GTT TCA TCC TGG AGC TTC TGC CTC A -3'(reverse) [20] and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) with primers 5'-GCC TCA AGA TCA TCA GCA ATG C-3' (forward) and 5'-CCA CGA TAC CAA AGT TGT CAT GG-3' (reverse) [21]. The expression of GAPDH was used to normalize the levels of the total RNA used in the assays.…”
Section: Reverse Transcriptase (Rt) Pcr Analysismentioning
confidence: 99%
“…Therefore, NT2 cells are often used as cell models for cancer therapy and neuron differentiation studies (5)(6)(7). Currently, cisplatin, fisetin and nucleoside drugs are applied to NT2 cell treatment.…”
Section: Introductionmentioning
confidence: 99%